2019
DOI: 10.1002/ece3.5891
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial genomes and genetic structure of the Kemp's ridley sea turtle (Lepidochelys kempii)

Abstract: The Kemp's ridley (Lepidochelys kempii) is the world's most endangered sea turtle species and is primarily distributed in the Gulf of Mexico. In the United States, South Padre Island, Texas serves as a key nesting ground for the species. Genetic studies of the Kemp's ridley have been used to aid in conservation and management practices, with the mitochondrial control region as the most commonly used marker due to its perceived hypervariability and ease of sequencing. However, with the advent of next generation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 45 publications
0
23
0
Order By: Relevance
“…Although this population went through a significant bottleneck, genetic diversity for the species in both nesting females (Frey et al, 2014;Frandsen, Figueroa & George, 2020) and immature individuals (this study) appears stable. Kemp's ridleys continue to face multiple threats, however, including increased mortality as by-catch in commercial fishing activities in the past two decades (Putman, Hawkins & Gallaway, 2020) and environmental disasters such as the Deepwater Horizon oil spill that disproportionately affected Kemp's ridleys (Shaver et al, 2021).…”
Section: Conservation Implicationsmentioning
confidence: 67%
“…Although this population went through a significant bottleneck, genetic diversity for the species in both nesting females (Frey et al, 2014;Frandsen, Figueroa & George, 2020) and immature individuals (this study) appears stable. Kemp's ridleys continue to face multiple threats, however, including increased mortality as by-catch in commercial fishing activities in the past two decades (Putman, Hawkins & Gallaway, 2020) and environmental disasters such as the Deepwater Horizon oil spill that disproportionately affected Kemp's ridleys (Shaver et al, 2021).…”
Section: Conservation Implicationsmentioning
confidence: 67%
“…Analysis of mitochondrial DNA from Lk15 (mitochondrial sequence obtained from non-enriched whole genome sequencing data from this sample) along with other published Kemp’s ridley mitochondrial D-loop control regions showed that Lk15 grouped within the haplotype 1 sub-group ( Figure 4 ). Since previous research shows that Kemp’s ridley turtles along the east coast of the United States are 80% likely to be haplotypes 1 and 2 (predominantly haplotype 1), and that 79% of haplotypes 1 and 2 originate from rookeries along the Texas coast [ 43 ], we can infer that Lk15 likely originated from Texas. These conclusions are based on currently available literature and may be subject to change, since Kemp’s ridley haplotype data are currently limited for regions other than Texas [ 43 , 44 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Since previous research shows that Kemp’s ridley turtles along the east coast of the United States are 80% likely to be haplotypes 1 and 2 (predominantly haplotype 1), and that 79% of haplotypes 1 and 2 originate from rookeries along the Texas coast [ 43 ], we can infer that Lk15 likely originated from Texas. These conclusions are based on currently available literature and may be subject to change, since Kemp’s ridley haplotype data are currently limited for regions other than Texas [ 43 , 44 , 45 ]. Phylogenetic analysis of ChHV5 UL30 and HP32 gene segments (described in detail in Section 3.4 ) suggests that this turtle harbored a Florida variant of ChHV5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both species migrate internationally, and conservation biologists have been able to identify and track subpopulations through sequence differences in mitochondrial DNA (mtDNA). Due to female philopatry, in which pregnant females usually return to the beaches where they hatched, and because mtDNA is maternally inherited, individual haplotypes can be associated with specific beaches of origin (Allard et al, 1994;Duchene et al, 2012;Patricio et al, 2017;Frandsen et al, 2020). Combining the genetic data with GPS and satellite tracking reveals migratory pathways for sea turtles (Dutton et al, 2019;Gredzens and Shaver, 2020).…”
Section: Introductionmentioning
confidence: 99%